2006
DOI: 10.1073/pnas.0510960103
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide mediates the rapid phase of febrile response to IL-1β

Abstract: IL-1␤ was identified after a long search for the endogenous pyrogen. It acts by inducing synthesis of prostaglandin E 2, which mediates the late phase of IL-1␤-induced fever. Here we show by radiotelemetry that the early phase of the fever response to IL-1␤ is mediated by ceramide. Hypothalamic application of the cellpenetrating C2-ceramide mimics the rapid phase of the IL-1␤-induced fever. Inhibition of ceramide synthesis blocks the rapid phase of fever but does not affect the slower prostaglandin E 2-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 35 publications
4
55
0
2
Order By: Relevance
“…This is mediated by the activation of Src family protein tyrosine kinases, which is effected by neutral sphingomyelinase-generated ceramides. The activation of neutral sphingomyelinase involves the recruitment of the scaffolding protein MyD88 to the agonist-charged IL-1 receptor complex [60]. In the present study, we observed the involvement of ceramide in IL-1β-mediated suppression of BDNF signaling.…”
supporting
confidence: 64%
“…This is mediated by the activation of Src family protein tyrosine kinases, which is effected by neutral sphingomyelinase-generated ceramides. The activation of neutral sphingomyelinase involves the recruitment of the scaffolding protein MyD88 to the agonist-charged IL-1 receptor complex [60]. In the present study, we observed the involvement of ceramide in IL-1β-mediated suppression of BDNF signaling.…”
supporting
confidence: 64%
“…There are at least five types of Smases, including the ubiquitous lysosomal acid SMase, the zinc-dependent secreted acid SMase, a neutral, Mg 2+ -dependent SMase, a neutral Mg 2+ -independent SMase, and an alkaline SMase. Neutral sphingomyelinase 2 (nSMase2) is a brain-specific nSMase that is thought to be located on the inner leaflet of the plasma membrane and is activated by phosphatidylserine and cellular stressors including the inflammatory cytokines TNFα, IL-1, Fas-L, UV irradiation, the neurotoxic HIV-proteins gp120 and Tat, and amyloid β (Brann et al 1999;Sortino et al 1999;Haughey et al 2003;Castiglione et al 2004;Lee et al 2004;Sanchez-Alavez et al 2006). Once nSMase2 is active, sphingomyelin shifts to the innerleaflet of the plasma membrane, where it can be catabolized to ceramide.…”
Section: Discussionmentioning
confidence: 99%
“…The thermosensitivity of PO/AH neurons is a plastic property both in vivo and in vitro. It has been found that the thermosensitivity can change rapidly in the presence of the pyrogens PGE2 [4] or IL-1 [5,6]. Slower changes are observed in some warm-sensitive PO/AH neurons which decrease their thermosensitivity during NREM sleep [7].…”
Section: Hypothalamic Control Of Thermoregulationmentioning
confidence: 99%
“…We have shown that prostaglandin E2 (PGE2), a well established endogenous pyrogen, increases the thermosensitivity and firing rates of PO/AH neurons by decreasing the frequency of IPSPs [4]. In contrast, IL-1β hyperpolarizes a different set of PO/AH neurons and reduces their thermosensitivity by increasing the frequency of IPSPs and of miniature IPSPs [5,13].…”
Section: Hypothalamic Control Of Thermoregulationmentioning
confidence: 99%
See 1 more Smart Citation